2012
DOI: 10.1002/bdra.22882
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional folic acid use: Still room to improve

Abstract: The knowledge about folic acid has declined over recent years, and the use during the recommended period did not improve since the survey of 2005. Based on this survey, there is still room for improvement in the knowledge and actual use of folic acid before pregnancy. Attention to these aspects should focus on younger, low-educated women and should include information about family planning and contraceptives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 78 publications
(66 reference statements)
3
12
0
Order By: Relevance
“…The lack of change in attitude could be caused either by the intervention not being effective or by a ceiling effect (a score of 4·5 on scale of 6 may leave little room for improvement). The latter explanation and the contribution of increased knowledge match findings in other studies: that hardly any objections against use of FA supplements are found, but also that, although many women know something about FA supplements, especially knowledge on when to start taking FA supplements is relatively low (2) . In the present study we did not test at the individual level for association between theoretical determinants of behaviour (knowledge, attitude) and intention or use of FA.…”
Section: Discussionsupporting
confidence: 83%
“…The lack of change in attitude could be caused either by the intervention not being effective or by a ceiling effect (a score of 4·5 on scale of 6 may leave little room for improvement). The latter explanation and the contribution of increased knowledge match findings in other studies: that hardly any objections against use of FA supplements are found, but also that, although many women know something about FA supplements, especially knowledge on when to start taking FA supplements is relatively low (2) . In the present study we did not test at the individual level for association between theoretical determinants of behaviour (knowledge, attitude) and intention or use of FA.…”
Section: Discussionsupporting
confidence: 83%
“…In the Netherlands, 37% of women in a multi-ethnic population in Rotterdam in 2002-06 and 65% of women attending some antenatal clinics in 2009 in the northern region started folic acid use before pregnancy. 13,14 In national birth cohorts, this proportion was 30% in Denmark 6 and 20% in Norway. 7 However, these studies may have overestimated folic acid use because of selection bias with a higher likelihood of inclusion for women with higher educational levels and those with a strong interest in health issues.…”
Section: Discussionmentioning
confidence: 98%
“…This resulted progressively in a high level of folic acid use. 13,18,25 It also The campaigns to promote folic acid should target specifically women planning their pregnancies. 28 They accounted for about three-quarters of the women who gave birth in our study and also for a substantial proportion of women in other European countries.…”
Section: 16mentioning
confidence: 99%
“…A possible cause for this may be the high percentage of unplanned pregnancies in Poland. A study of Woude et al showed that periconceptional folic acid supplementation during the recommended period was used significantly more often by women who planned pregnancy [15]. Low compliance with periconceptional folic acid intake recommendations may also be associated with inadequate knowledge of young women about the character and the complications of NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this survey we have intentionally selected women with higher education since several studies revealed that such population is most compliant with recommendation of folacin supplementation [15,33]. This data suggests that efficacy of the folic acid education campaign in women without university education can be even less satisfactory.…”
Section: Discussionmentioning
confidence: 99%